Manajemen Pesantren Berbasis Kearifan Lokal di Pesantren Rakyat Al-Amin Sumberpucung Malang - Ragil Arwani; Ahmad Zainuri (Ta'lim : Jurnal Multidisiplin Ilmu, 2025)
Pesantren which is the oldest institution in Indonesia, has various uniqueness to be researched. The pattern of education also tends to be the same from time to time, namely through approaches based on local wisdom of the community. Likewise, the Al-Amin People's Islamic Boarding School in Sumberpucung District, Malang Regency, which is able to develop formulations in governance based on the values of usefulness for the surrounding community. Therefore, this study is intended to explain the management of Islamic boarding schools based on local wisdom which is focused on the education governance system of Islamic Boarding Schools based on local wisdom. The method in the study uses a descriptive-qualitative approach with data collection through in-depth interviews, participant observations, and documentation. The results of the research can be concluded that the Islamic Boarding School Management System is based on Local Wisdom at the stage of planning activities based on community potential while involving all elements of society through a poll that is conducted with the principle of anywhere, anytime and with anyone. The activities that have been formulated target several aspects, namely (1) curriculum aspects, including the selection of teaching staff from community competencies and learning content oriented to the development of cultural arts, entrepreneurship development, agriculture and livestock; (2) economic aspects, including the establishment of Islamic boarding school barns, savings for students and the surrounding community; (3) institutional aspects that include the establishment of formal education as a support system for early childhood education